Vinhos da região serrana do Espírito Santo : composição, análise sensorial e avaliação das boas práticas de elaboração - Rodrigues, Leticia Karina (2017)
Wine production has expanded in the mountain region of Espírito Santo, which in 2014 was classified as a grape production zone destined for industrialization. This region is exploited by agrotourism and has as its characteristic the artisanal production of wines, whose profile meets the preference of the Brazilian consumer who seeks products of accessible value and sweet palate. The current emerging panorama of Espírito Santo in the national scenario as a grape producer, and the precariousness of data and information on the capixaba production of “table wines”, encouraged the exploration of the theme. Thus, the objectives of this work were to identify the conditions in which wines are prepared, as to the adequacy to the standard of identity and quality (PIQ) advocated by the Ministry of Agriculture, Livestock and Food Supply (MAPA); Lifting hygienic sanitary conditions of manufacturing; As well as to analyze the sensorial profile of “table wines” produced in artisanal and industrial scale. For physical-chemical and sensory parameters, 48 samples of wines made with american and / or hybrid grape varieties from harvests between 2010 and 2016 were evaluated from 19 canteens located in 05 municipalities in the mountain region of Espírito Santo which were also submitted to the evaluation of Good Manufacturing Practices (GMP). The samples were composed of red and white wine, of the soft, demi-sec and dry classes, elaborated with 10 distinct varieties of grapes in the varietal form or as an assemblage (mixtures). The results obtained in the analyzes show that 60% of the studied samples present at least one item that was disapproved in the physico-chemical analysis considering the PIQ established by the current legislation of the MAPA. The sensorial profile of the samples was quite different from each other. This variation can be related to the great diversity of products supplied spontaneously by the winemakerss according to their production line, which made it impossible to apply the comparative analyzes between products of different classes, different vintages and produced with the most varied assemblages of grapes. The assessment of compliance with GMP by means of a weighted score calculation found that 22% of the canteens were in excellent or very good hygienic conditions, 22% in good conditions, 33% in regular conditions and 22% in poor sanitary conditions. It is worth noting that the deviations found can be treated by means of the application of suitable oenological techniques, treatment of the vineyards with the use of the available technologies and with adequacy to the GMP. The present research found that the viticulture of the mountain region of Espírito Santo still has much to develop and a long way to go in search of a quality standard that meets the requirements of current legislation and with the guarantee of consumer safety. There is a need for specialized technical support in the sector, government incentive, training and awareness of the vine grower, for the success and expansion of the wine production chain in the State.